The impact of gamma and electron beam irradiation sterilization technology on the pigments and phenolic components of saffron - Mohammad Reshad; Seyed Pezhman Shirmardi; Hosein Afarideh; Samira Shahbazi; Hamed Askari (Scientific Reports)
Abstract Dried stigmas of saffron with the natural contaminant microflora were irradiated at five dose levels (1, 2, 3, 4 and 5 kGy) via a gamma and electron beam irradiator. The changes in the microbial population (total count, mold and yeast and coliform contamination), total phenolic content (TPC), antioxidant activity (AOA), bitterness, aromatic, and coloring strengths of saffron after radiation were investigated. Additionally, phenolic compounds and carotene glycosides were assayed via high–performance liquid chromatography (HPLC). Irradiation effectively eliminated microbial populations, with doses above 2 kGy resulting in no detectable fungi or bacteria. Additionally, radiation treatments had little effect on the crocin (color), picrocrocin (bitterness) and safranal (aroma) indices measured by the ISO 3632 procedure. On the other hand, the HPLC results revealed that major carotenoids (Picrocrocin, trans-4-GG-crocin, trans-3-Gg-crocin, cis-4-GG-crocin, trans-2-gg-crocin, trans-crocetin, and safranal) and phenolic compounds (catechol, salicylic acid, p-hydroxybenzoic acid, vanillin, gentisic acid, gallic acid, caffeic acid, syringic acid, ferulic acid, and p-coumaric acid) in saffron can experience undesirable changes in attributes due to high doses of radiation. Specifically, a gamma dose of 1 kGy and an electron beam dose of 2 kGy were found to be optimal for reducing the microbial load, with minimal damage to color, flavor, and phenolic and antioxidant compounds. Additionally, a high dose of radiation has a profound effect on the stability and concentration of phenolic compounds in saffron, potentially altering its antioxidant properties and overall quality. This study highlighted the effectiveness of low doses of gamma and electron beam irradiation in eliminating microbial loads and enhancing product quality.